ENTORNO FAMILIAR Y PROBLEMAS CONDUCTUALES EN LAS/LOS ESTUDIANTES DE LA ESCUELA DE EDUCACIÓN BÁSICA “IV CENTENARIO” DE LA CIUDAD DE LOJA - Rodas Cartuche, Katty Maribel (2019)
The present research work focuses on a study carried out to the students, parents and teachers of the Basic Education school "IV Centenario" of the city of Loja, where it is revealed how the family environment influences the state behavior of the students. The school plays an important role in the academic process of formation and improvement, however the family is the fundamental basis for the personal and spiritual growth of the child, which is why the study focuses basically on the educational trilogy, the which allowed to know results about: the causes and effects of negative behaviors generated by the behavioral state in students as well as explain how the family environment influences these behaviors, whose general objective is to contribute with a proposal of social intervention through actions that allow the improvement of behavioral status in children. The main findings were obtained through the use of methods such as the scientific, inductive, deductive, analytical and synthetic methods and the techniques used were interviewing, direct observation and focus groups applied to students, parents, teachers, psychologist and director of the school of basic education "IV Centenary of the city of Loja. The results determine that the causes that cause behavioral problems in children are due to the type of family environment, since many of them live in conflictive and dysfunctional environments, overprotection and time spent caring for their children. children are scarce since some parents are the main economic support of their homes and work daily, so they leave their children under family care or in extreme cases are left alone at home, another of the causes is the influence of the relationships of the peer groups given in the school. What has caused the prevalence of behavioral problems in students such as: violent behavior, hyperkinetic, disruptive behavior and avoidance or lack of socialization, another effect is low academic performance, school dropouts and emotional problems (low self-esteem). 5 The students' behavioral problems are also influenced by the family environment, since in a large percentage it is due to family problems, where there are disorganized and dysfunctional homes, domestic violence, drug use, parents in prison and divorces. At the same time, the little trust and communication between parents and children and the absence of norms and rules in the home have provoked rebelliousness, disobedience and opposition in children. To this is added the little interest and concern of parents in the education of their children since most do not attend school, nor establish communication relationships with teachers. Therefore, together with these results, a "Proposal for intervention with the aim of improving the behavioral status of students through strategies and actions that allow family strengthening" is proposed from the social work approach, aimed at students, parents and teachers of the institution through workshops, training and activities with a participatory and experiential methodology, with the aim of creating spaces for reflection and participation in those involved.